(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The purpose of this article is to demonstrate that arbitration awards have access to the real folio regardless of the issuance of an arbitration letter by the Judiciary, considering that the Arbitration Law expressly establishes that the arbitration award produces, between the parties and their successors, the same effects of the sentence rendered by the bodies of the Judiciary Power and, being condemnatory, constitutes an enforceable title, which is corroborated by the Code of Civil Procedure, which lists the arbitration award as a kind of judicial enforcement instrument. Although it is not expressly provided for in the exhaustive list of titles that can be registered in the real estate registry provided for in article 221 of the Public Registry Law, the arbitration award has the same legal nature as the award rendered by the bodies of the Judiciary Branch and must be accepted by acknowledging this nature.